Stainless steel 316lhydroxyapatite composite via metal injection moulding : properties study - Nurul Ain, Johari (2021)
Hydroxyapatite (HA) is well-known as bio-active ceramic and biological affinity with bony tissue which appointed as a selected material applied in bone surgery. The similarity of phase composition and chemical to inorganic phase in bones makes the HA ceramic as the best biocompatibility of all orthophosphates. However, HA has low mechanical properties which limits it to be use as implant materials. Stainless steel 316L (SS 316L) metallic biomaterial has blossomed as the most favorable metal used in biomedical application due to excellent mechanical and corrosion properties. Uniting HA with higher mechanical properties of metallic biomaterials 316L stainless steel (SS 316L) to produce a SS 316L/HA bio composite has been as the best alternative to form an acceptable mechanical property for human implants. The SS 316L/HA composite would have credited vital to current implant materials such as low Young’s modulus, high biocompatibility and bio-inertless. This research investigated the mechanical, physical and corrosion properties of the SS 316L/HA composite by additive of HA via metal injection moulding technique (MIM). Commercial HA was produced from calcium-phosphate. While, Polypropylene (PP), Stearin Acid (SA) and primary binder, Paraffin Wax (PW) utilized as binder system. The composite of SS 316L/HA was prepared at different weight ratio of HA (0,5,10 and 15 wt.%). All compacts were sintered at 1350 ºC for 3 hours of soaking time. The physical properties of SS 316L/HA sintered compact were investigated by the shrinkage and relative density study. The mechanical properties of the sintered SS 316L compacts were determined by the microhardness and tensile testing. While, the corrosion properties were characterised by electrochemical experiments. The investigation indicated on SS 316L and HA powders showed an average particle size were 11.2μm and 70.3μm which recorded the Sw values of 3.0 and 2.0 respectively. This showed that metal and ceramic powders broad particle size distribution and fit for moulding. The shrinkage and density increased as the increase of HA amount. While, the tensile strength and hardness decreased with the additive of HA in composite compacts. While, The corrosion rate increased as the HA amount increased. The observation on microstructure by optical microstructure study (OM) showed the additive of HA on composite compacts routed the porosity amount increased. While, the grain boundaries decreased as the additive of HA increased. Microstructure observation revealed the circular pore formation tendencies which changed to irregular shape as the HA additive. Moreover, this shows the improvement on sintered compact properties which brought the decreasing of mechanical properties as it routes closer to the human bone mechanical properties. Hence, it can be concluded that with powder ratio of HA wt.% additive is critical parameter for improving mechanical properties and with 5 to 10 wt. % of HA additive showed the best ratio of SS 316L/HA biocomposite.